Adipose tissue biomarkers of fatty acid intake - Baylin, Ana (2002)
The use of biomarkers to assess dietary intake has increased dramatically in the past few years (1-7). Biomarkers may provide a more accurate and objective measure of long-term intake than dietary questionnaires provide because biomarkers do not rely on memory, self-reported information, or interviewer bias. However, nutrient concentrations in tissue or blood do not always reflect dietary intake because they can be affected by genetic factors, smoking, obesity, physical activity, and metabolism